Which Kind of and How Much Disruption to the Symmetry of Double-Slit is Necessary to Produce the Fringe Pattern Changes as Conjectured to Have Seemingly Manifested Psychophysical Faculty? - Piao, Daqing (Journal of Scientific Exploration, 2023)
Identifying the most plausible cause of the fringe pattern changes in the double-slit of psychophysical domain (Radin et al., 2012, 2013) not only is instrumental to the understanding of the nature of psychophysical effects that may manifest but also will shed light on the effecting mechanism of such anomalous faculty should it be quantifiable. We implement computer simulations of double-slit fringe patterns based on the Huygens–Fresnel principle using the primary experimental geometrical parameters of Radin et al. (2013) to assess how an asymmetry of the double-slit configuration could affect the fringe visibility. The main result is that the normalized interference fringe corresponding to an asymmetry of the electrical field magnitude of 3/1 or 1/3:1 as was modeled by Radin et al. (2013) is grossly indifferent from that caused by an asymmetry of the spectral bandwidth of 0.00205 nm between the two slits at 632.8 nm center wavelength. A spectral broadening of 0.00205 nm of the light for the experimental setting utilized by Radin et al. (2013) could correspond to a power change of no more than 10 picowatts. Further studies are warranted to test this hypothesis towards understanding the nature of psychophysical faculty as was conjectured with Radin’s double-slit experiments.